Kinetic rationale for selectivity toward N- and C-terminal oxygen-dependent degradation domain substrates mediated by a loop region of hypoxia-inducible factor prolyl hydroxylases. - Flashman, E; Bagg, E; Chowdhury, R; Mecinović, J; Loenarz, C; McDonough, M; Hewitson, K; Schofield, C (2008)
Hydroxylation of two conserved prolyl residues in the N- and C-terminal oxygen-dependent degradation domains (NODD and CODD) of the alpha-subunit of hypoxia-inducible factor (HIF) signals for its degradation via the ubiquitin-proteasome pathway. In human cells, three prolyl hydroxylases (PHDs 1-3) belonging to the Fe(II) and 2-oxoglutarate (2OG)-dependent oxygenase family catalyze prolyl hydroxylation with differing selectivity for CODD and NODD. Sequence analysis of the catalytic domains of the PHDs in the light of crystal structures for PHD2, and results for other 2OG oxygenases, suggested that either the C-terminal region or a loop linking two beta-strands (beta2 and beta3 in human PHD2) are important in determining substrate selectivity. Mutation analyses on PHD2 revealed that the beta2beta3 loop is a major determinant in conferring selectivity for CODD over NODD peptides. A chimeric PHD in which the beta2beta3 loop of PHD2 was replaced with that of PHD3 displayed an almost complete selectivity for CODD (in competition experiments), as observed for wild-type PHD3. CODD was observed to bind much more tightly to this chimeric protein than the wild type PHD2 catalytic domain.